2008
DOI: 10.2353/ajpath.2008.070920
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the Nipple to Hair-Bearing Epithelia by Lowering Bone Morphogenetic Protein Pathway Activity at the Dermal-Epidermal Interface

Abstract: Epithelial appendages , such as mammary glands and hair , arise as a result of epithelial-mesenchymal interactions. Bone morphogenetic proteins (BMPs) are important for hair follicle morphogenesis and cycling and are known to regulate a wide variety of developmental processes. For example , overexpression of BMPs inhibits hair follicle formation. We hypothesized that the down-regulation of the BMP signaling pathway in the basal epidermis expands regions that are competent to form hair follicles and could alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…The development of the APSU occurs in coordinated fashion, no doubt because of crosstalk between the differentiating epithelial cells and underlying mesenchyme, as well as differences in signaling pathways and receptors of the hair follicle, apocrine gland, and sebaceous gland (Hatsell and Cowin, 2006;Andrechek et al, 2008;Mayer et al, 2008). The apocrine gland duct typically opens into the infundibulum of the hair follicle, such that secretion contacts the hair shaft.…”
Section: The Evolution Of Mammary Secretionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of the APSU occurs in coordinated fashion, no doubt because of crosstalk between the differentiating epithelial cells and underlying mesenchyme, as well as differences in signaling pathways and receptors of the hair follicle, apocrine gland, and sebaceous gland (Hatsell and Cowin, 2006;Andrechek et al, 2008;Mayer et al, 2008). The apocrine gland duct typically opens into the infundibulum of the hair follicle, such that secretion contacts the hair shaft.…”
Section: The Evolution Of Mammary Secretionmentioning
confidence: 99%
“…In 2002, I hypothesized that this must be due to the inhibition of hair follicle development in the vicinity of mammary glands, and suggested that if the presumptive inhibiting compound (s) could be blocked at the earliest stages of mammary development, hair follicles may develop in association with mammary buds (Oftedal, 2002b). Although the actual signaling pathways are undoubtedly complex, with both shared and differing sensitivities to signaling compounds among different epithelial cell types, it is intriguing that bone morphogenetic proteins (BMPs) inhibit hair follicle formation, and that when Mayer et al (2008) reduced BMP signaling in the mouse by transgenic overexpression of a BMP antagonist, nipple epithelium was converted into pilosebaceous units. Mayer et al (2008) hypothesized that the BMP pathway had been co-opted during evolution of the nipple to suppress hair follicle formation.…”
Section: The Evolution Of Mammary Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, inhibition of BMP signaling with the soluble antagonist Noggin can convert nipple epithelia into hair follicles (23). However, BMPR2-DN mice were found to have normal histopathology with luminal epithelial cells fully migrated to the distal tip of the fat pad (Fig.…”
Section: Inhibition Of Bmp Signaling In the Mammary Gland Did Not Affectmentioning
confidence: 99%
“…Notably, the BMP antagonist Noggin stimulates Lef1 up-regulation at the hair placode and promotes follicle formation (Botchkarev et al 1999;Jamora et al 2003). Intriguingly, transgenic mice overexpressing Noggin not only show increased hair density, but also a nearly complete substitution of eccrine glands by hair follicles in the normally hairless footpads (Plikus et al 2004) and ectopic hair follicles in the normally hairless nipple epithelium (Mayer et al 2008). These findings suggest that inhibiting BMP signaling favors hair follicle cell fates, whereas active BMP signaling promotes glandular cell fates.…”
Section: Bmp Signaling Pathwaymentioning
confidence: 99%